ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FLUKTUASI NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA DI INDONESIA - Risda Sinta Dewi; Syamsu Alam; Andi Samsir; Abd Rahim; Regina Regina (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The phenomenon of globalization increases the intensity of interconnection among countries worldwide, so that the demand of each country is determined by the nature of its foreign trade. Undoubtedly, to conduct international business, the common currency, the US Dollar, must be used, as every country uses the dollar as a medium for transactions with one another. This increases the risk that changes in exchange rates themselves can lead to changes in currency values. The exchange rate of the Rupiah has a significant impact on the commercial efforts of individuals and organizations by comparing the value of one country's money with that of another. Indonesia's participation in the global economy exposes it to negative impacts from export and import activities and inflation, which influences the value of the Rupiah. This research aims to determine how exports, imports, and inflation affect the volatility of the Indonesian Rupiah exchange rate against the US Dollar. This study employs a quantitative model approach using data sourced from government agencies, namely BPS (Central Statistics Agency) and BI (Bank Indonesia). The research shows that the independent variables used (exports, imports, and inflation) have a simultaneous effect on the value of the Rupiah. The Rupiah exchange rate is greatly influenced by the export and import variables but is not affected by the inflation variable. The coefficient of determination (R²) is 84.1%. This indicates that exports, imports, and inflation are factors that can cause changes in the value of the Rupiah against the US Dollar.